The Role of the Pusaka Djakarta Silat School for the Community of Menteng atas from 2015 to 2022 - Yuni Maryuni; Maryuni Maryuni; Tubagus Umar Syarif Hadi Wibowo; Muhammad Ibnu Fadillah (International Journal Labs, 2026)
This study aims to examine the role of the Djakarta Heritage Silat College (PSPD) for the people of Menteng Atas, Setiabudi District, South Jakarta, in the 2015–2022 period. The research used a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation. The informants were selected purposively, consisting of six sources who had direct involvement with the PSPD. The results of the study showed that PSPD carries out three main functions: (1) as a non-formal educational institution that implements a holistic curriculum covering technical, physical, mental, moral, and socio-cultural aspects; (2) as an agent of the preservation of Betawi culture in the midst of modernization and globalization; and (3) as an effective social control mechanism in fostering the younger generation to avoid deviant behaviour. PSPD also plays a role in building student achievement orientation through participation in pencak silat championships of various levels. Based on Soerjono Soekanto's role theory, PSPD has actively carried out its rights and obligations, making a real contribution to character development, strengthening local cultural identity, and improving the quality of social life of the people of Menteng Atas.